Beneficial soil bacterium Bacillus subtilis (GB03) augments salt tolerance of white clover - Han, Qing-Qing; Lü, Xin-Pei; Bai, Jiang-Ping; Qiao, Yan; Paré, Paul W.; Wang, Suo-Min; Zhang, Jin-Lin; Wu, Yong-Na; Pang, Xiao-Pan; Xu, Wen-Bo; Wang, Zhi-Liang (Frontiers in Plant Science, 2014)
Soil salinity is an increasingly serious problem worldwide that reduces agricultural output potential. Selected beneficial soil bacteria can promote plant growth and augment tolerance to biotic and abiotic stresses. Bacillus subtilis strain GB03 has been shown to confer growth promotion and abiotic stress tolerance in the model plant Arabidopsis thaliana. Here we examined the effect of this beneficial soil bacterium on salt tolerance in the legume forage crop, white clover. Plants of white clover (Trifolium repens L. cultivar Huia) were grown from seeds with or without soil inoculation of the beneficial soil bacterium Bacillus subtilis GB03 supplemented with 0, 50, 100 or 150 mM NaCl water into soil. Growth parameters, chlorophyll content, malondialdehyde (MDA) content and osmotic potential were monitored during the growth cycle. Endogenous Na+ and K+ contents were determined at the time of harvest. White clover plants grown in GB03-inoculated soil were significantly larger than non-inoculated controls with respect to shoot height, root length, plant biomass, leaf area and chlorophyll content; leaf MDA content under saline condition and leaf osmotic potential under severe salinity condition (150 mM NaCl) were significantly decreased. Furthermore, GB03 significantly decreased shoot and root Na+ accumulation and thereby improved K+/Na+ ratio when GB03-inoculated plants were grown under elevated salt conditions. The results indicate that soil inoculation with GB03 promotes white clover growth under both non-saline and saline conditions by directly or indirectly regulating plant chlorophyll content, leaf osmotic potential, cell membrane integrity and ion accumulation.